Effects of the ınquiry-based learning method on students’ Achievement, science process skills and attitudes towards science: A meta-analysis science - Aktamış, Hilal; Hiğde, Emrah; Özden, Barış (Journal of Turkish Science Education, 2016)
The effectiveness of inquiry-based learning method was discussed for a long time. However, inquirybased learning method was not discussed and compared with traditional learning before in terms of students’ academic achievement, science process skills and attitudes towards science in a meta-analysis study. This study aimed to cover the effects of the inquiry-based science education on students’ academic achievement, science process skills and attitudes towards science comparing with traditional learning. The study reviews the findings of the studies on the effectiveness of the inquiry-based science education comparing with traditional learning. In other words, meta-analysis method was used to combine statistically the numerical data of the studies and to reach a general conclusion using the results of these studies. The study reviewed a total of nineteen studies (37 comparisons in terms of achievement, science process skills and attitudes towards science) about the effects of the inquiry-based science education on the students’ academic achievement, science process skills and attitudes towards science comparing with traditional learning carried out in Turkey between 2005 and 2015. Meta-analysis results showed that the inquiry-based science education had a positive and higher levels of effects of students’ academic achievement (Cohen’s d=1.029). It was also found that this specific teaching and learning method had a positive and medium level of effect on their science process skills (Cohen’s d=0.742) and attitudes towards science (Cohen’s d=0.558). It was found that the inquiry-based learning method used in science education had much more significant effects on student achievement rather than on their science process skills and their attitudes towards science in contrast to the traditional teaching method